Sustainable retirement village for older people: a case study in Brisbane, Australia - Xia, Bo; Zuo, Jian; Skitmore, Martin; Chen, Qing; Rarasati, Ayomi (International Journal of Strategic Property Management, 2015)
Retirement villages are regarded as a viable accommodation option for the ever increasing ageing population in Australia. This paper aims to identify sustainability features and practices adopted in retirement villages and associated benefits to improve the life quality of older people. A case study of an existing retirement village 10 kms from Brisbane CBD was conducted involving a series of interviews with the village managers and residents together with documents relating to the village's operations and activities. The environmentally friendly features that were incorporated into the development mainly include green design for the site and floor plan and waste management in daily operation. More importantly, a variety of facilities are provided to strengthen the social engagement and interactions among the residents. Additionally, different daily services are provided to assist independent living and improve the health conditions of residents. Also, the relatively low vacancy rate in this village indicates that these sustainability features offer good value of money for the residents. The paper provides a first look at sustainable retirement villages in terms of triple bottom line sustainability with emphasis on social aspects, reveals the importance in maintaining an appropriate balance, and provides examples of how this can be achieved in practice.First Publish Online: 19 Jun 2015